Trauma-informed supervision in the disaster context. Issue 1 (2nd January 2018) - Adamson, Carole
ABSTRACT: Supervision is increasingly defined by reflection and traumainformed knowledge and practice. When faced with a disaster, the role and function of supervision is changed by the scale of events, with psychosocial support for traumatic stress often side-lined by, or subsumed within, emergency interventions. Disasters, however, need a longitudinal focus on recovery for many years following; this focus provides the logic for supervision at every stage of a disaster. In this article, the author defines disaster and its phases, and raises issues for supervision within the disaster context. Hypothetical examples are used both from the author's location in Aotearoa New Zealand and from disasters more internationally familiar.